117k views
1 vote
Can someone help me please

Can someone help me please-example-1
User Stiin
by
6.1k points

1 Answer

4 votes

For this case we must indicate an expression equivalent to:


x + 2 + [4x- \frac {x ^ 2 + 6x + 8} {x + 4}]

If we factor the quadratic expression, we must find two numbers that when multiplied give as result 8, and when summed give as result 6. These numbers are 4 and 2. Then:


x ^ 2 + 6x + 8 = (x + 2) (x + 4)

Rewriting the expression:


x + 2 + [4x- \frac {(x + 2) (x + 4)} {(x + 4)}] =

Simplifying common terms we have:


x + 2 + [4x- (x + 2)] =

Taking into account that:


- * + = -\\x + 2 + 4x-x-2 =\\x-x + 2-2 + 4x =\\4x

ANswer:

4x

User Linsek
by
6.1k points